PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, RASIO HUTANG DAN PROFITABILITAS TERHADAP TARIF PAJAK EFEKTIF (Studi Empiris pada Perusahaan Perbankanyang terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Khurin’in Kurnia Putri; Raja Adri Satriawan Surya; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study is to examine the effect of corporate governance, firm size, debt ratio and profitability on effective tax rate on banking companies listed in IDX (Indonesia Stock Exchange) during the period 2013-2015.The sample in this study consisted of 23 banking companies in IDX (Indonesia Stock Exchange) during the period 2013-2015 were selected based on certain criteria by using purposive sampling. With 3-year observation period for the sample amounted to 69 samples. The analytical method used is multiple linear regression analysis with t test and the coefficient of determination were processed using SPSS program. The partial regression test (t test) proves that corporate governance, firm size and debt ratio has significant negative effect to effective tax rate. While profitability has significant positive effect to effective tax rate.The results of the coefficient determination (R²) showed that 59,7% of the variation in effective tax rate can be explained by the independent variable, while the remaining 40.3% is explained by other variables that are not in this study.Keywords: effective tax rate, corporate governance, firm size, debt ratio, profitability